Evaluation in social work : the art and science of practice - Unrau, Yvonne A. (Oxford University Press, 2007)
Social work practice is founded upon the linkage between the objectives and goals of clients, programs, and agencies. This book provides an introduction to program evaluation couched within the quantitative and qualitative traditions - the two approaches commonly used to generate relevant social work knowledge.